Erythrocyte levels in chronic obstructive pulmonary disease (COPD) patients with a history of positive and negative COVID-19 - Siti Nur Chasanah; Aslani Thereestiana Sari; Djamila Zakaria; Ayutia Safira Rusidana Thalib (Acta Biochimica Indonesiana)
Background: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory condition that predisposes patients to severe complications when infected with SARS-CoV-2 (COVID-19). Hematological alterations, particularly in erythrocyte levels, may influence the clinical course and outcomes in these high-risk individuals. Objective: This study aimed to evaluate the erythrocyte profile of COPD patients with and without COVID-19 at RS Paru Dr. Ario Wirawan Salatiga.